2009
DOI: 10.21273/hortsci.19.3.593
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Evaluation of Cut Dahlia, Linaria, Lupine, Poppy, Rudbeckia, Trachelium, and Zinnia

Abstract: Vase life of ‘Karma Thalia’ dahlia (Dahlia ×hybrida), ‘Lace Violet’ linaria (Linaria maroccana), ‘Sunrise’ lupine (Lupinus hartwegii ssp. cruickshankii), ‘Temptress’ poppy (Papaver nudicaule), ‘Indian Summer’ rudbeckia (Rudbeckia ×hybrida), ‘Jemmy Royal Purple’ trachelium (Trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…The characteristics of cut dahlia flowers during postharvest handling have previously been reported by Shimizu-Yumoto and Ichimura (2013), who demonstrated that a 6-benzylaminopurine (BA) spray treatment extended the vase life of some cultivars. Moreover, some researchers have reported that treatment with sugars or antibacterial agents also extends the vase life of cut dahlia flowers (Dole et al, 2009;Takahashi et al, 2016), although these studies were limited to only a few cultivars and did not clarify how bacterial proliferation or a deficiency of carbohydrates affect vase life. Moreover, the form of the dahlia flower is a type of bloom on the stem of a plant known as a capitulum that is common in Asteraceae plants.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of cut dahlia flowers during postharvest handling have previously been reported by Shimizu-Yumoto and Ichimura (2013), who demonstrated that a 6-benzylaminopurine (BA) spray treatment extended the vase life of some cultivars. Moreover, some researchers have reported that treatment with sugars or antibacterial agents also extends the vase life of cut dahlia flowers (Dole et al, 2009;Takahashi et al, 2016), although these studies were limited to only a few cultivars and did not clarify how bacterial proliferation or a deficiency of carbohydrates affect vase life. Moreover, the form of the dahlia flower is a type of bloom on the stem of a plant known as a capitulum that is common in Asteraceae plants.…”
Section: Introductionmentioning
confidence: 99%
“…Most evaluations of ethylene sensitivity have been performed on mature plants or on detached organs (i.e., fruits or cut flowers) (Archambault et al, 2006;Dole et al, 2009;Goto et al, 1999;Serek et al, 1994Serek et al, , 1995van Doorn, 2001van Doorn, , 2002Woltering, 1987;Woltering and van Doorn, 1988). A few studies have used the seedling triple response to evaluate differences in ethylene sensitivity between plants (Clark et al, 2001;Edelman et al, 2014;Lanahan et al, 1994).…”
mentioning
confidence: 99%
“…Woltering and van Doorn (1988) concluded that dahlias were slightly sensitive to ethylene. Moreover, Dole et al (2009) found that 'Karma Thalia' dahlias were unaffected by an ethylene exposure of 16 h at 1 μL L −1 . However, Kato et al, (2002) found that Campanula medium flowers were unaffected after exposure to ethylene at 10 μL L -1 for 16 h, but all flowers wilted after exposure to ethylene at 2 μL L -1 for 48 h. Therefore, longer exposure to ethylene may affect dahlias as well and the response may be related to the stage of development when exposed to ethylene.…”
Section: Introductionmentioning
confidence: 97%
“…Ideally therefore flowers need to last for 10-14 days overall. Previous work indicates that the dahlia flower may reach a vase life of up to 10 days (Dole et al, 2009) however, the commercial practicalities of this have yet to be examined.…”
Section: Introductionmentioning
confidence: 99%